1993
DOI: 10.2466/pr0.1993.73.3f.1291
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity Data for a Chinese Translation of the Center for Epidemiological Studies-Depression

Abstract: A translated version of the CES-Depression scale attained a reliability coefficient alpha of 0.92 in a group of 30 adult Chinese persons with noninsulin-dependent diabetes mellitus. Fifteen percent of the sample scored 16 or above, which has been noted as indicative of depression in U.S. samples. The validity of the instrument was assessed through an in-depth content analysis and through convergent validity analyses. Comparison of depression scores of this sample with those from English-speaking Occidentals sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 16 publications
1
56
1
Order By: Relevance
“…We assessed depression using the Chinese version of the Center for Epidemiologic Studies Depression (CES-D) scale, a self-report depression scale for research in the general population [34]. Participants were asked to indicate the frequency of symptoms on a 4-point scale (0=less than a day; 1=1 to 2 days; 2=3 to 4 days; 3=5 to 7 days) within the last week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed depression using the Chinese version of the Center for Epidemiologic Studies Depression (CES-D) scale, a self-report depression scale for research in the general population [34]. Participants were asked to indicate the frequency of symptoms on a 4-point scale (0=less than a day; 1=1 to 2 days; 2=3 to 4 days; 3=5 to 7 days) within the last week.…”
Section: Methodsmentioning
confidence: 99%
“…Among all of the questionnaires above, IPAQ-C, quality of life, and depression had been well developed and validated in Chinese versions in previous studies [25,33,34]. The English questionnaires addressing motivational, volitional, and distal indicators of behavior change were translated into Chinese by a bilingual researcher.…”
Section: Methodsmentioning
confidence: 99%
“…Those measures not available in Mandarin were translated using standard translation and back-translation procedures. 16 The survey also included questions that assessed the availability of family members to assist with HIV care and caregiving support provided as well as details about the patients' relationships with their caregivers, including frequency of contact, living arrangement, and type of care received. Adherence was assessed by using the Simplified Medication Adherence Questionnaire (SMAQ), a six-item patient self-report measure, which has shown strong reliability.…”
Section: Survey Componentmentioning
confidence: 99%
“…Lin (1989) used the CES-D as the basis for a new scale to form the Chinese Depressive Symptom Scale and also reported that the CES-D scale is a valid instrument for Chinese research when compared to quality of life factors. Rankin et al (1993) claimed the CES-D scale has good internal consistency reliability to diabetic Chinese in San Francisco.…”
Section: Depression (Ces-d)mentioning
confidence: 99%